Cell-Mediated Immune Responses After Administration of the Live or the Recombinant Zoster Vaccine: 5-Year Persistence. (27th November 2021) - Johnson, Michael J; Liu, Cuining; Ghosh, Debashis; Lang, Nancy; Levin, Myron J; Weinberg, Adriana
Abstract: We compared glycoprotein E (gE)- and varicella zoster virus (VZV)-specific Th1 immunity in 160 adults, aged 50–85 years, randomized to receive live or recombinant zoster vaccine (RZV). gE-specific responses measured by interferon-γ (IFN-γ) and interleukin 2 (IL-2) dual-color Fluorospot were significantly higher at all time points postimmunization in RZV recipients. VZV-specific IL-2+ memory, but not IFN-γ+ or IFN-γ+IL-2+ effector responses, were higher in RZV recipients at ≥3 months postimmunization. Only RZV recipients maintained higher postvaccination gE-specific IL-2+ and IFN-γ+ and VZV-specific IL-2+ responses for 5 years. The 5-year persistence of VZV-specific memory and gE-specific Th1 immunity may underlie superior RZV efficacy. Clinical Trials Registration NCT02114333.